Harmonization Of Religious and State Law In The Context Of Siri's Marriage: A Case Study In Bogor Regency - Miladina, Rifaatun (Pusat Pengkajian dan Pengembangan Islam Jakarta (PPIJ), 2025)
Siri marriage, as a legally valid marriage practice but not recorded in the state administration, raises legal and social problems, especially for the protection of women and children. This study aims to analyze the perception and practice of siri marriage among religious leaders understand their role in shaping social legitimacy towards this practice. Using a qualitative approach with a legal-social framework, data were collected through in-depth interviews and participatory observation of five religious leaders in Bogor Regency. The study results show that religious leaders hold cultural and spiritual authority in facilitating siri marriage, with the primary motivation being economic reasons, social pressure, and the meaning of Islamic law. Although some figures have begun to realize the importance of legal records, there is still tension between religious norms and state regulations. This study recommends increasing legal literacy and collaborative dialogue between the government and religious leaders as a strategy for legal harmonization. The implications of this study are essential for developing a family policy that is fair, inclusive, and harmonized between religious law and state law.